Homeostasis of the Intraparenchymal-Blood Glutamate Concentration Gradient: Maintenance, Imbalance, and Regulation - Bai, Wei; Zhou, Yuan-Guo (Frontiers in Molecular Neuroscience, 2017)
It is widely accepted that glutamate is the most important excitatory neurotransmitter in the central nervous system (CNS). However, there is also a large amount of glutamate in the blood. Generally, the concentration gradient of glutamate between intraparenchymal and blood environments is stable. However, this gradient is dramatically disrupted under a variety of pathological conditions, resulting in an amplifying cascade that causes a series of pathological reactions in the CNS and peripheral organs. This eventually seriously worsens a patient’s prognosis. These two “isolated” systems are rarely considered as a whole even though they mutually influence each other. In this review, we summarize what is currently known regarding the maintenance, imbalance and regulatory mechanisms that control the intraparenchymal-blood glutamate concentration gradient, discuss the interrelationships between these systems and further explore their significance in clinical practice.